No effect of the cyclooxygenase‐2 inhibitor etoricoxib on pre‐emptive and post‐operative analgesia in visceral surgery: results of a randomized controlled trial. (31st March 2015) - Fleckenstein, J.; Kohls, N.; Evtouchenko, E.; Lehmeyer, L.; Kramer, S.; Lang, P.M.; Siebeck, M.; Mussack, T.; Hatz, R.; Heindl, B.; Conzen, P.; Rehm, M.; et al.
Abstract: Background: Pre‐emptive analgesia in perioperative care has potential benefits for patients. The pre‐emptive and postoperative analgesic effects of the cyclooxygenase‐2 inhibitor etoricoxib have been investigated using a 2 × 2 factorial trial design. Methods: According to the 2 × 2 factorial study design, 103 patients scheduled for visceral surgery, were randomly allocated to two groups prior to surgery. Patients could receive either etoricoxib or placebo (to investigate pre‐emptive analgesia). Subsequent to surgery, patients randomly received either etoricoxib or placebo, again. It follows, that four treatment modalities (continuous or replaced intervention) result, to investigate postoperative analgesia. Main Outcome Measure was the cumulative morphine use 48 h post‐surgery. Other outcomes included pain intensities, pain thresholds and sensory detection. Results: Eighty‐six patients (female n  = 42; mean age 53.82 ± 13.61 years) were evaluated on the basis of an intention to treat analysis. Pre‐emptive administration of 120 mg etoricoxib did not significantly reduce the cumulative morphine dose within the first 48 h after surgery, when compared to the administration of placebo. The analysis of the post‐operative treatment groups showed a non‐significant 8% reduction in morphine dose during the continuous administration of etoricoxib. There were no changes in sensory perception as detected with QST before and after surgery or between groups. Conclusions: The effect of administering etoricoxib was not superior to placebo in reducing the morphine dose required for postoperative analgesia. The lack of changes in peripheral nociception suggests that central algetic mechanisms are of higher impact in the development of postoperative pain following abdominal or thoracic surgery.